The dark side of foreign firm presence: How does the knowledge spillover from foreign direct investment influence the new venture performance - Huan Wang; Leven Jianwen Zheng; Zuopeng Zhang; Abhishek Behl; Varsha Arya; Marjan Kuchaki Rafsanjani (Journal of Innovation & Knowledge (JIK), 2023)
This study presented a comprehensive framework to explain how the knowledge spillover from foreign direct investment (FDI) influences domestic new venture performance. Referring to external (formal and informal institutional distances) and internal (foreign experience and learning orientation) factors, this study examined the external and internal factors as moderators in this relationship. Data were collected from 103 Chinese new ventures and China's inward FDI for 2017. The findings revealed that the negative competitive effect caused by foreign firms outweighs the FDI knowledge spillover effect. The results also indicated that external factors significantly influence the impact of foreign firms' presence on the new venture performance, whereas the influence of internal factors was limited. The study highlighted the importance of incorporating the heterogeneity of domestic firms into FDI knowledge spillover research.
Keywords: 650; Cultural distance; Foreign direct investment; Institutional distance; Knowledge spillover; New venture